Water Resources Management In Order To Fulfil The Basic Needs Of The Community - Indrati Rini (Badan Penerbit STIEPARI Press, 2024)
Water resources are a basic need of the community that must be fulfilled by the state. The fulfillment of water resources carried out by the central government and local governments have not been fulfilled to the maximum. There are several reasons the state is given the authority to manage water resources, and the way the government fulfills water resources as a basic need of the community, as well as the reality of the sufficiency of water resources in the community. The need for water resources, if it has not fulfilled met as a whole, then strategic steps are needed to overcome it.